GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 18030 species occurrences available in GBIF matching the query: TaxonKey: Pseudorasbora parva (Temminck & Schlegel, 1846) HasCoordinate: true. The dataset includes 18030 records from 68 constituent datasets: 21 records from International Barcode of Life project (iBOL). 121 records from Royal Dutch Angling Association (SVN) - Piscaria. 63 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Yser in Flanders, Belgium. 2 records from National Taiwan Ocean University. 34 records from Fishbase. 666 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 1 records from Inventario Español de Especies Terrestres (MAGRAMA). 1226 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 30 records from The Fish Collection at the Zoologische Staatssammlung München. 1 records from Données ONF Faune-Flore-Fonge. 36 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 2 records from Zoological collection of the National Museum. 4 records from Museum of Comparative Zoology, Harvard University. 23 records from Ichthyology Collection - Royal Ontario Museum. 118 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 32 records from Monitoring data from the federal state Hesse (Germany). 3 records from iNaturalist Research-grade Observations. 7 records from National Taiwan University. 1 records from Alien Species in Poland - Animals. 1 records from National Museum Of Marine Science & Technology. 16 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 192 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 23 records from CAS Ichthyology (ICH). 151 records from Monitoring data from the federal state Saxony (Germany). 1 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 573 records from Freshwater fishes of Italy. 12 records from Atlas of Danish Fishes. 3 records from naturgucker. 928 records from VIS - Post 2013 - Fishes in estuarine waters in Flanders, Belgium. 44 records from Fish monitoring data in Lake Kasumigaura. 1 records from LACM Vertebrate Collection. 32 records from Ichthyology, Kagoshima University Museum. 2 records from Akita Prefectural Museum＋Actinopterygius Specimens of Akita Prefectural Museum. 423 records from Fish collection of the Museum of Nature and Human Activities, Hyogo. 3 records from NMNH Extant Specimen and Observation Records. 10551 records from VIS - Fishes in inland waters in Flanders, Belgium. 3 records from UWFC Ichthyology Collection. 24 records from Fish Collection of Yokosuka City Museum. 266 records from Fish specimen database of Osaka Museum of Natural History. 2 records from Fish collection of National Museum of Nature and Science. 1 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 4 records from VerteCAT: Banco de datos de vertebrados de Cataluña. 12 records from Life Science National Tsing Hua University. 1 records from UCM Fish Collection (Arctos). 1 records from KUBI Ichthyology Collection. 26 records from Gunma Museum of Natural History, Fish Specimen. 1 records from Biological and palaeontological collection and observation data MNHNL. 3 records from Collection Pisces SMF. 344 records from Geographically tagged INSDC sequences. 825 records from VIS - Reference freshwater monitoring in Flanders, Belgium (post 2013). 356 records from Trekvis - Migratory fishes in the river Scheldt. 334 records from Inventaire National du Patrimoine Naturel : Atlas des poissons d'eau douce de France métropolitaine (2011). 93 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 15 records from The Fish Database of Taiwan. 5 records from National Taiwan Museum. 1 records from Données ONF Faune-Flore-FOnge. 1 records from Australian Museum provider for OZCAM. 12 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 1 records from Fish Fauna of Berlin. 1 records from Colección de referencia de otolitos, Instituto de Ciencias del Mar-CSIC. 200 records from Invasive species - American bullfrog (Lithobates catesbeianus) in Flanders, Belgium. 2 records from UF FLMNH Ichthyology. 1 records from Taiwan Fisheries Research Institute – Digital archives of coastal and offshore specimens. 3 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 3 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 5 records from Ichthyology. 41 records from National Museum of Natural Science. 96 records from Freshwater fishes of the Western Balkans. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences